Pengaruh Penerapan E-System Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Salah Satu Kantor Pelayanan Pajak Pratama Di Kota Bandung - Nia Kurniawati; Vicky Achmad Zulfikar; R. Deni Purana; Djajun Juhara (Acman: Accounting and Management Journal, 2022)
This study aims to determine the effect of the application of the E-Taxation System on the Compliance of Individual Taxpayers at KPP Pratama Bandung Cicadas. The research method used is a descriptive analysis method, while the data collection technique is by distributing questionnaires to 40 respondents (Individual Taxpayers) at the Bandung Cicadas Pratama Tax Service Office. The data analysis technique used is the person product-moment correlation coefficient analysis technique, simple linear regression analysis, and the coefficient of the determination analysis technique, with his assistance using the help of excel and software SPSS 26 for windows. In the results of the regression research, there is a significant and positive effect between tax collection actions and individual taxpayer compliance. These results are calculations from the regression analysis obtained from Y = 8.74+ 0,803 X, which shows a constant value of 8,749; this shows that if the application of the E-Taxation System is zero, then the level of compliance with individual taxpayers is 8,749 while the predictive value is 0.803. shows that for each additional unit for the Implementation of the Tax E-System, the individual taxpayer compliance will increase by 0.803 and fall into the "Probably" category. That is, there is a robust relationship between the implementation of the Tax E-System with individual taxpayer compliance, with a determination coefficient of 66.3%. The application of the E-Taxation System affects individual taxpayer compliance by 66.3%, while the remaining 33.7% is the influence of other factors not examined in this study.